A study of vague language in argumentative essays by Thai EFL undergraduate students - Mana Termjai (Penerbit Universiti Kebangsaan Malaysia, 2025)
This research investigated the use of vague language (VL) in argumentative essays written by Thai undergraduate students studying English as a foreign language (EFL). It aimed to explore the extent of VL usage, identify typical VL forms, and propose strategies to address its use in writing. The participants comprised 36 third-year English major students from a government university in Thailand enrolled in the Persuasive and Argumentative Writing course. The research instrument was the final exam paper from this writing course, which required students to compose an argumentative essay. The study revealed a significant prevalence of VL in the essays, with four typical forms identified: general nouns, indefinite pronouns, vague quantifiers, and general verbs. Additionally, the study proposed practical resolutions to address the use of VL in academic writing. These findings emphasise the significance of providing explicit instruction on using clear, precise, and specific language, alongside other linguistic elements, to enhance students’ academic writing skills, clarity, and effectiveness in written expression.